2005
DOI: 10.1093/eurheartj/ehi432
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of pre-hospital combination-fibrinolysis plus conventional care with pre-hospital combination-fibrinolysis plus facilitated percutaneous coronary intervention in acute myocardial infarction

Abstract: In patients with STEMI, additional facilitated PCI after pre-hospital combination-fibrinolysis results in an improved tissue perfusion with subsequent smaller infarct size as opposed to pre-hospital combination-fibrinolysis alone. This translates into a trend towards a better clinical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0
5

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(55 citation statements)
references
References 36 publications
0
50
0
5
Order By: Relevance
“…Twelve larger randomized studies and metaanalyses (LOE 1) 438 -449 and 2 smaller randomized studies 450,451 consistently reported better clinical outcome with use of glycoprotein IIb/IIIa inhibitors compared with placebo. This result was supported by many studies which consistently reported better outcomes with upstream or early use of glycoprotein IIb/IIIa inhibitor compared with deferred treatment or other strategies (LOE 1 [452][453][454][455][456][457][458][459][460][461][462][463][464][465][466][467] ; LOE 2 468 -473 ; LOE 3 474 ; LOE 4 [475][476][477][478] ; LOE 5 479 ).…”
Section: Consensus On Sciencementioning
confidence: 99%
“…Twelve larger randomized studies and metaanalyses (LOE 1) 438 -449 and 2 smaller randomized studies 450,451 consistently reported better clinical outcome with use of glycoprotein IIb/IIIa inhibitors compared with placebo. This result was supported by many studies which consistently reported better outcomes with upstream or early use of glycoprotein IIb/IIIa inhibitor compared with deferred treatment or other strategies (LOE 1 [452][453][454][455][456][457][458][459][460][461][462][463][464][465][466][467] ; LOE 2 468 -473 ; LOE 3 474 ; LOE 4 [475][476][477][478] ; LOE 5 479 ).…”
Section: Consensus On Sciencementioning
confidence: 99%
“…In a recent comparative study of ST-segment resolution by thrombolytic versus primary coronary intervention (PCI), showed the resolution of ST-segment by thrombolytic are as follows: Complete 51.9%, partial 26.6% and failed resolution in 21.5% acute myocardial infarction patients after 90 min of initiation of fibrinolytic therapy (Thiele et al, 2005). By using the same resolution criteria, in our study we observed the similar results in non-diabetic myocardial infarction where 48.4% patients showed complete resolution, 31.7% patient's partial resolution and 19.8% showed failed In our study, more 'complete ST-resolution' was seen in non-diabetic patient (48.4 vs. 19.7%; Z= 4.25; p<0.001) whereas type 2 diabetic subjects were presented with significantly higher incidence of failed ST-resolution than non-diabetic subjects (67.2 vs. 19.8%; Z= 6.79; p<0.001).…”
Section: Discussionmentioning
confidence: 99%
“…The Leipzig Prehospital Fibrinolysis Group randomized 164 patients within 6 hours of STEMI onset in the prehospital setting to reteplase plus abciximab alone or reteplase plus abciximab and transfer for immediate PCI. 24 The primary end point of infarct size assessed by delayed-enhancement magnetic resonance was reduced in the immediate PCI arm (median, 5.2% versus 10.4%; Pϭ0.001), and the composite clinical end point of death, reinfarction, major bleeding, or stroke at 6 months tended to be reduced with immediate PCI compared with fibrinolysis alone (15% versus 25%; Pϭ0.10). In the Combined Angioplasty and Pharmacological Intervention Versus Thrombolysis Alone in Acute Myocardial Infarction (CAPITAL AMI) trial, 170 STEMI patients treated with tenecteplase within 6 hours of symptom onset were randomized to routine immediate PCI or conservative care with rescue or deferred PCI as clinically indicated.…”
Section: Fibrinolysis With Versus Without Immediate Routine Pcimentioning
confidence: 99%
“…16,20 In contrast to these historical studies, 7 contemporary prospective, modest-sized randomized trials have been published and collectively demonstrate that routine PCI with stent implantation in the early hours after fibrinolysis may be beneficial compared with a strategy of delayed routine or ischemia-driven PCI. [22][23][24][25][26][27][28] In the Primary Angioplasty in Patients Transferred From General Community Hospitals to Specialized PTCA Units With or Without Emergency Thrombosis (PRAGUE) trial, 300 patients within 6 hours of STEMI onset were randomized at hospitals without PCI facilities to streptokinase alone, streptokinase plus transfer for immediate PCI, or transfer for primary PCI. 22 Figure 1.…”
Section: Fibrinolysis With Versus Without Immediate Routine Pcimentioning
confidence: 99%
See 1 more Smart Citation